Proceedings of the First International Conference on Concrete Block Paving, Newcastle-upon-Tyne, 2-5 September 1980 - International Conference on Concrete Block Paving (1st : 1980 : Newcastle-upon-Tyne); Jeffrey, Hayden (Newcastle : University of Newcastle-upon-Tyne, 1982)
08